Pengembangan Produk Panna Cotta Bir Pletok Berbahan Dasar Jahe Merah (Zingiber Officinale Var. Rubrum), Serai (Cymbopogon Citratus) Dan Kayu Secang (Caesalpinia Sappan) - Annisa Rizkiriani; Vieta Annisa Nurhidayati; Ani Nuraeni; Astari Riski; Syahidah Endrini An Najihah; Siti Munawarah (Program Studi Gizi UNSIKA, 2022)
Pletok beer is a traditional Indonesian drink made from ginger, lemongrass, sappanwood and other spices with high antioxidant content. Pletok beer is currently less popular toyoung consumers. The modification of the Pletok beer product in the form of panna cotta isexpected to increase the value of Pletok beer among consumers. This study aimed to findPletok Beer Panna Cotta formulation preferred by the consumers. The study used acompletely randomized design with three treatments. Formula 1, 2, and 3 are panna cottaproducts with main additives, namely whipping cream, plain milk, and heavy cream,respectively. Hedonic test was performed to 30 untrained panelists using a 5-scale Likertquestionnaire with indicators assessing appearance, color, taste, aroma, and texture. The testresults showed that formula with added ingredients of plain milk have better preference scoresin color and appearance, while formulas with added ingredients of heavy cream have betterpreference scores in taste and texture. Overall, the formulation of Beer Pletok Panna Cottafavored by the panelists were products with heavy cream added or Formula 3.